Technicians and Artisans of Heaven-and-Earth : Imperial Memories of Diviners, Physicians, and Craftsmen from Mid-Medieval China - Kory, Stephan N., (Asian Studies E-Books Online, Collection 2025., 2025)
Technicians and Artisans and Heaven-and-Earth reconstructs memories of significant but often overlooked figures from a remarkably diverse yet understudied period of Chinese history. The book includes translations of three biographical collections from the official dynastic histories of the Northern Wei, Northern Zhou, and Sui featuring the lives of "technicians and artisans." Through a comparative, intertextual, and literary analysis of these works, Stephan N. Kory not only sheds light on the roles and functions of diviners, physicians, and craftsmen in the imperial courts of mid-medieval North China, but also provides us with fascinating insights into medieval Chinese court life and society.